Combination of low cost terrestrial and aerial photogrammetry: three-dimensional survey of the church of San Miguel in Ágreda (Soria) - Zaira Peinado Checa; Angélica Fernández Morales; Luis Agustín Hernández (Virtual Archaeology Review)
Nowadays, one of the most used methods for the architectural survey is photogrammetry. The combination of terrestrial and aerial photogrammetry of low altitude is the ideal method for obtaining global geometric documentation of any building, as it collects information about concealed or inaccessible points. The UAV or drone is the device currently most used to capture aerial photographs. We used the example of the Church of San Miguel in Agreda to establish a methodology for data collection and the process for obtaining a textured three-dimensional model.